Pendamping Travelling: Kajian Antropologi Sosial tentang Mahram - Maimun, Muhammad (Musawa Jurnal Studi Gender dan Islam, 2010)
This anthropologi.cal study of mahram aims to analyze why a culture prohibits marriage between siblings and marriage between a parent and a child. The term is recognized as incest marriage or in Islam those relationships constitute mahram. In Islam as exemplified in the Qur'an and had.its, mahram is not only about forbidden marriage system, but also about something else, like women's travelling. Theoretically, incest might menace human life bio"logically and against the public common good. In the context travelling of women with mahram, term of mahram has specific roles as the protector for travelling member offamily, just as how it functions in a marriage institution itself. However, understanding a hadith about mahram, that a woman is prohibited to travel but with her mahram, should not only about the availability of a mahram, but also about safety and comfort system, about social network, and friendship. In hajj or pilgrimage, the establishedfriend ship and cooperation of formal and non-formal organization might function as the supporting framework of security and safety system for women.